2019
DOI: 10.1016/j.tem.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuins in Metabolic and Epigenetic Regulation of Stem Cells

Abstract: Sirtuins are highly conserved NAD +-dependent enzymes that are capable of removing a wide range of lipid lysine acyl-groups from protein substrates in a NAD +-dependent manner. These NAD +-dependent activities enable sirtuins to monitor cellular energy status and modulate gene transcription, genome stability, and energy metabolism in response to environmental signals. Consequently, sirtuins are important for cell survival, stress resistance, proliferation, and differentiation. In recent years, sirtuins are inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 90 publications
(112 reference statements)
1
32
0
1
Order By: Relevance
“…Mechanistically, these classes are zinc-dependent and referred to as 'classical HDACs' [6,7]. In contrast, class III HDACs (sirtuins 1-7) are NAD + -dependent [8]. The biological role of HDACs is to generate and maintain the balance between protein (histone) acetylation and deacetylation.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, these classes are zinc-dependent and referred to as 'classical HDACs' [6,7]. In contrast, class III HDACs (sirtuins 1-7) are NAD + -dependent [8]. The biological role of HDACs is to generate and maintain the balance between protein (histone) acetylation and deacetylation.…”
Section: Introductionmentioning
confidence: 99%
“…16 Sirtuin proteins are involved in regulation of metabolism, proliferation, differentiation and cell survival. 17 SIRT1 protein prevents intestinal inflammation by regulating the gut microbiota. 18 SIRT1 deficiency in the intestine specifically activates secretory cells, as is evident by the elevated number of intestinal Paneth and goblet cells without alteration of other cell types or the proliferation rate of IECs.…”
mentioning
confidence: 99%
“…This mechanism, which links metabolic and stress changes with epigenetic modifications of the DNA, is of special relevance to maintaining genomic integrity (Bosch-Presegue and Vaquero, 2015). This mechanism has been suggested to be fundamental for regulating epigenetic processes in stem cells (Fang et al, 2019). Ryall et al (2015) showed in vitro by using cultured mouse SCs and in vivo by using SIRT1 deacetylase domain ablation mouse models that the shift from fatty acid oxidation to glycolytic metabolism in activated SCs produces less intracellular NAD+ and consequently less SIRT1 activity, which ultimately leads to histone acetylation and the activation of muscle-specific gene transcription that promotes myogenesis ( Figure 1B).…”
Section: Metabolic Regulation Of Satellite Cells During Regenerationmentioning
confidence: 93%